The family Conidae from Peruvian Sea - Paredes, Carlos (2010)
This paper describes and provides information on the species of the genus Conus (Neogastropoda:Conidae) preserved in the Laboratorio de Biología y Sistemática de Invertebrados Marinos de la Facultad de Ciencias Biológicas (LaBSIM) y el Museo de Historia Natural de la Universidad Nacional de San Marcos (MUSM). The material was collected at the Department of Tumbes (9 locations) and Piura (16 locations). Intesive collect was realized in April 2007 and occasional in posterior years. Of the 16 reported species it is counted with material corresponding to 11 of them: Conus (Conus) gladiator Broderip, 1833; Conus (Asprella) arcuatus Broderip & Sowerby, 1829; Conus (Cylinder) lucidus Wood, 1828; Conus (Leptoconus) poormani Berry, 1968; Conus (L.) recurvus Broderip, 1833; Conus (Pyruconus) fergusoni ;Sowerby, 1873; Conus (P.) patricius Hinds, 1843; Conus (Ximeniconus) mahogani Reeve,1843; Conus (X.) perplexus Sowerby, 1857; Conus (X.) tornatus Sowerby, 1833 and Conus (X.) ximenes Gray, 1839. There are no material of Conus (C.) princeps Linnaeus, 1758; Conus (C.) tiaratus Sowerby, 1833; Conus (Chelyconus) purpurascens Sowerby, 1833; Conus (Leptoconus) regularis Sowerby, 1833 and Conus (L.) virgatus Reeve, 1849. Conus kohni MacLean & Nybakken, 1979 and Conus xanthicus Dall, 1910, are reported for the first time, wich increases to 18 the number of species registered for the tropical sea of Peru.